Effectiveness of the daily and weekly doses of iron supplementation in pregnancy and puerperium on Haemoglobin and iron status at 6 weeks postpartum - Hyder, S.M. Ziauddin; Persson, Lars-Ake; Chowdhury, AMR; Lonnerdal, B; Ekstrom, Eva-Charlotte (BRAC Research and Evaluation Division (RED), 2019)
Objective: Describe the effectiveness of continuous daily and weekly doses of iron supplementation during pregnancy and puerperium on haemoglobin and iron status at 6 weeks postpartum. Design: An iron supplementation trial conducted at antenatal care centre (ANCC) assigned randornly_·either to the daily (lx60-mg) or weekly (2x60-mg) doses of iron supplementation. Setting: Fifty community-based ANCCs in a rural area of Bangladesh. Subjects: In the trial, 209 pregnant women during second trimester were recruited. Fifty-one were lost to follow-up and the final sample size consisted of 158 women (daily n=72 and weekly n=86). Intervention: Each woman in the daily group received I tablet (60 mg Fe) per day and in the weekly group 2 tablets (120 mg Fe) per week. Intake of iron tablets was monitored by the MEMS~ during 11 weeks in ~pregnancy. Haemoglobin was assessed on venous blood by HemoCue~, serum concentrations of ferritin by radio immunoassay and serum transferrin receptors by immunoassay double sandwich method. Results: At 6 weeks postpartum, haemoglobin and iron status did not differ between the two supplementation groups. However, an overall improvement in haemoglobin and iron status was observed compared to the baseline status. Women who took 2:40 tablets in 11 weeks had higher haemoglobin (P=0 .05) and SFt (P=0.04) and lower sTfR (P=0.32) at 6 weeks postpartum. Conclusions: A lack of difference in response was observed between the daily and weekly doses of iron supplementation. Higher number of iron tablet intake during pregnancy and puerperium was associated with better haemoglobin and iron status at 6 weeks postpartum. Sponsorship: SIDA/SAREC, Sweden and BRAC, Bangladesh. Descriptors: Anaemia, iron deficiency, daily weekly supplementation. postpartum, Bangladesh